Factors Causing Stunting in Toddlers in Gunung Baran Village, Panyabungan District, Mandailing Natal Regency - Doriani Harahap; Nurkholidah (International Journal of Public Health Excellence (IJPHE), 2023)
Stunt on child reflect condition fail grow on child consequence from chronic malnutrition, so child be too short for especially her age in the first 1,000 days of life (HPK). This study aims to determine factors that cause stunting in toddlers based on a lack of caregivers well, health services are still limited including ANC services, lack of coverage nutritious food, lack of clean water and sanitation coverage, economic status, LBW. Type study This characteristic descriptive with technique total sampling with amount 30 respondent. From the results of research based on the knowledge of the majority of knowledgeable mothers Enough as much 20 respondent. based on nanny Which not enough Good majority good knowledge as many as 24 respondents (80%), based on limited service ANC majority knowledgeable Good as much 21 respondent (70%), based on lack of access family food nutritious majority knowledgeable Enough as much 19 respondents (63.33%), based on the family's lack of access to clean water and sanitation majority knowledgeable Good as much 13 respondent (43.33%), based on status the majority of the economy is knowledgeable enough as many as 15 respondents (50%), based on LBW majority have child normal as much 26 respondent (86.67%). Results From the analysis it can be concluded that mothers are knowledgeable enough, but do not use it enough knowledge the so from That Mother can Mother can clarify benefit Which important For health And to power health so that more maximum in give promotion health to Mother about factor reason happening stunting